Karakteristik Pori dan Hubungannya dengan Permeabilitas pada Tanah Vertisol Asal Jeneponto Sulawesi Selatan - Masria Masria; Christianto Lopulisa; Hazairin Zubair; Burhanuddin Rasyid (Jurnal Ecosolum, 2018)
This study aims to determine the characteristics of soil pores and therelationship of pore characteristics with soil permeability. Soil samples were collected from Punagaya Village, Bangkala District, Jeneponto Regency, South Sulawesi. Soil samples were taken from 20 observation points representing two types of land use ie cultivated land and fallow field at a depth of 0-60 cm. Soil analysis (pH, organic material, C-organic, cation exchange capacity, bulk density and soil texture), Pore characteristics(porosity, pore distribution and pore stability), and permeability. Analysis of soil properties and pore characteristics was descriptive, while the relationship between pore characteristics and permeability was analyzed by single or multiple regression and correlation analysis. The results showed that the permeability of soil vertisol 0.29 cm/h (slow) and the average value of soil pore characteristics of vertisol as follows: porosity ranged 56.49%, fast drainage pore 4.35%, water pore available 17.8% And 32.5% micro pores, and 36.46% pore stability. Based on the regression and correlation test, it is known that Porosity and porosity and pore stability index have the greatest influence on permeability.